An effective global agricultural research systemdepends on a strong contribution at national level - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
An effective global agricultural research system depends on a strong contribution at national levelThe international scientific community aims to coordinate its agricultural research efforts within a global system which brings together the national...